Photodynamic therapy of psoriasis - E. V. Filonenko; V. Ivanova-Radkevich (Biomedical Photonics, 2023)
Photodynamic therapy (PDT) in the treatment of psoriasis remains the subject of much debate. There is no consensus in the scientific community about effective and safe PDT regimens for psoriasis. Described in the published materials doses and concentrations of photosensitizers for psoriasis, as well as light doses, differ by dozens of times. The purpose of this review is to analyze the efficacy and safety profile of various PDT regimens for psoriasis. Some studies demonstrate 100% effectiveness of the method in certain modes (complete or partial clearance of psoriasis foci after PDT). In particular, such efficiency was obtained with the application of 20% 5-ALA (light dose 15 J/cm2) and 0.1% methylene blue (light dose 15 J/ cm2). The main factor limiting the use of PDT in psoriasis, and in some cases even being the reason for treatment interruption, is severe pain during the irradiation procedure. This requires careful development of PDT regimens in patients with psoriasis.